Success of early antiviral monotherapy with pegylated interferon α-2a for posttransplantation fibrosing cholestatic hepatitis C (a clinical case) - A. V. Chzhao; O. I. Andreitseva; V. E. Syutkin; A. O. Chugunov; K. R. Dzhagrayev; A. A. Saliyenko; I. V. Aleksandrova; V. V. Artamonov; E. A. Soldatov; L. V. Donova; I. E. Galankina; L. N. Zimina (Трансплантология (Москва))
The paper describes a case of posttransplantation fibrosing cholestatic hepatitis C (PFCHC) in a female patient whose transplant was preserved due to timely antiviral therapy (AVT). Its differential diagnosis primarily required that chronic graft rejection and biliary anastomotic stricture be excluded as a cause of dysfunction. PFCHC was proposed to be a possible cause of graft dysfunction on the basis of the clinical course of the disease, the presence of a very high viral load, intervals after orthotopic liver transplantation, the results of histological studies, and no signs of biliary hypertension. Antiviral monotherapy was initiated using pegylated interferon α-2a (Pegasys), which resulted in a considerable improvement and yielded complete early virological and biochemical responses to AVT. This allows one to hope to obtain a sustained virological response and to eliminate hepatitis C infection in the patient after termination of a 48-week course of therapy.